Peningkatan Kesehatan Lansia Melalui Homecare - Ambo Hamsah, Idawati; Nur, Hamdan; Annizah, Febriyah (Yayasan Mandar Indonesia, 2021)
Elderly according to WHO is a person entering the age of 60 years and over. The increase in chronic diseases is most in the elderly population who require routine and long-term care to be appropriate if the care is carried out based on Homecare Sidodadi, Wonomulyo district, Polewali Mandar district, West Sulawesi province. This research method (mixed methods) with a questionnaire research instrument there are several questions about daily living (ADL) activities. The population is 247 elderly and a sample of 2 people with non-potential elderly inclusion criteria (bedrest). The research was carried out on May 25 to June 7 2021. The results showed that with the homecare service, muscle movement exercises, mobilization, physical exercise, and ROM positions in 2 respondents who had impaired physical mobility from 2 nonpotential respondents became 1 (50%) elderly potential and 1 (50%) of the other elderly become cared for elderly.